Number system (International Journal of Scientific Research and Management (IJSRM), 2023)
We use numbers in daily life without examining a pattern in numbers [1]. We solve problems through equations everyday without generalizing our results [2]. This happens because we do not express numbers simply enough to get a sense of the numbers. In other words, numbers are not expressed in terms of their occurrences to understand the numbers and express them in the same form. This paper expresses numbers in the form of their occurrences.